2011
DOI: 10.1159/000328202
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Large B Cell Lymphoma Complicating Total Knee Arthroplasty: Case Report and Literature Review of the Association of Diffuse Large B Cell Lymphoma with Joint Replacement

Abstract: Primary lymphoma of bone is extremely rare. There are increasing reports of lymphoma arising in bone adjacent to metallic prostheses. Herein, we describe the case of a 76-year-old man who developed diffuse large B cell lymphoma in the tibia 3 years after total knee arthroplasty for osteoarthritis. A review of the literature has identified 11 other cases of lymphoma arising in the context of orthopaedic metallic implants. To our knowledge this is the first reported case of a primary lymphoma arising in bone adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…The carcinogenic effects of the metallic components and wear particles are not yet fully elucidated [ 7 ]. Most cases reported in this context are DLBCL associated with chronic inflammation and concomitant EBV infection [ 2 , 7 ]. Campo et al report, that in these lesions lymphomas-infected cells frequently express a latency type 3 with positivity for the viral proteins latent membrane protein 1 and EBV nuclear antigen 2, suggesting, that the lymphoid proliferation may be related primarily to a decrease in the host immune-surveillance [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The carcinogenic effects of the metallic components and wear particles are not yet fully elucidated [ 7 ]. Most cases reported in this context are DLBCL associated with chronic inflammation and concomitant EBV infection [ 2 , 7 ]. Campo et al report, that in these lesions lymphomas-infected cells frequently express a latency type 3 with positivity for the viral proteins latent membrane protein 1 and EBV nuclear antigen 2, suggesting, that the lymphoid proliferation may be related primarily to a decrease in the host immune-surveillance [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our described case of DLBCL, however, lacks EBV infection and is localized to the knee without any other site of involvement. A summary of our literature search (see Table 1 ) showed only one case of diffuse large B-cell lymphoma in association with a joint replacement without EBV association and was published in 2011 [ 2 ]. Another case was reported with negativity for the EBV in situ hybridization, but positivity for EBV in the polymerase chain reaction [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have suggested there may be a cohort of metallic-joint prosthetic related lymphomas which could be likened to the well-recognised breast-implant associated anaplastic large cell lymphoma (ALCL). 3 This case discussion highlights the need for further international cohort studies that include a broad analysis of potential patient and prosthetic specific risk factors for malignancy.…”
Section: Diffuse Large B-cell Lymphoma Masquerading As a Prosthetic Jmentioning
confidence: 99%